Impact of dental National Partnership Agreements on public dental service waiting lists in Queensland - Ratilal Lalloo; Jeroen Kroon (Australian and New Zealand Journal of Public Health, 2017)
Abstract Objective: Analyse the Queensland Dental Public Service waiting list from 2013 to 2015 while various funding agreements between the federal and state and territory governments were in place. Methods: Queensland Public Dental Service waiting list is open data and is updated monthly. This analysis reports on the changing number of people waiting for care and the percentage of people waiting beyond the reasonable period. Results: While the number of people waiting decreased when funding was specifically allocated to “blitz the dental public waiting list”, these have since increased back to pre‐blitz period numbers. The percentage now waiting beyond the reasonable period has decreased from 57% to 28% over the study period. Conclusions: While the ‘blitz’ was successful in reducing waiting list numbers, this was not sustained. The deferred federal funding to states/territories for dental services may have worsened the situation. Implications for Public Health: While an injection of funds to reduce the waiting list is important and has had an impact, to adequately address oral health will require not just continuing funding, but also a shift away from the current curative ‘downstream’ approach towards a health‐promotive ‘upstream’ approach. This will reduce not only the cost of treatment, but also waiting lists.